Report of the Executive Board to the Board of Governors on Progress on the Fifteenth General Review of Quotas. (Policy Papers; Policy Paper, 2016)
In February 2016, the Board of Governors adopted Resolution No. 71-2 on the Fifteenth General Review of Quotas (hereafter the 'Fifteenth Review'), which (i) welcomed the entry into force of the Seventh Amendment on the Reform of the Executive Board, allowing the quota increases under the Fourteenth Review to become effective; (ii) urged the members who had not yet consented to their Fourteenth Review quota increases to do so without further delay and urged the members who had consented to their quota increases to make their quota payments in a timely manner; (iii) regretted that the Fifteenth Review had not been completed by December 15, 2015, as mandated by the Articles of Agreement and as requested in Board of Governors Resolution No. 70 1, and resolved to continue the Fifteenth Review under Article III, Section 2(a) and called on the Executive Board to work expeditiously on the Fifteenth Review in line with previous Executive Board understandings, and with the aim of completing the Fifteenth Review by the 2017 Annual Meetings; and (iv) requested that the Executive Board report to the Board of Governors on progress on the Fifteenth Review by the 2016 Annual Meetings and the 2017 Spring Meetings. This report responds to that request.